Biodegradable elastomers based on ABA triblocks : influence of end-block crystallinity on elastomeric character - Kong, Jen Fong (2013)
ABA triblock copolymers, based on biodegradable monomers, namely ε-caprolactone (CL) and L-lactide (LLA), were synthesized and studied. The end-blocks were mostly poly(L-lactide) while the middle segments were a random copolymer of PCL and PLLA. Synthesis of these copolymers was performed by varying the end-block segment length while retaining a fixed middle-block segment length and vice versa. Nuclear magnetic resonance studies confirmed the designed structure of the copolymers and their thermal properties were studied with differential scanning calorimetry. Mechanical and thermomechanical properties were determined with an Instron tester and by dynamic mechanical analysis, respectively. The elastomeric character of the copolymers was verified by cyclic test as well as by creep and recovery measurements. Changes made to the middle- and end-block segment lengths had a significant influence on the mechanical properties of the copolymers, especially their extendibility and recoverability. An increase in the crystallinity of the end-blocks in the copolymers caused a drop in their elastomeric character. In cyclic testing, under conditions of 50% and 150% strain, copolymers with low end-block crystallinity could recover more than 85% whereas copolymers with high crystallinity showed reduced recovery values as low as 60%.